PROFESSIONAL AND PEDAGOGICAL TRAINING OF TEACHERS IN THE CONTEXT OF EUROPEAN INTEGRATION PROCESSES - Olena Shuryn (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The process of vocational teacher training technologies in the context of European integration processes is investigated. The theoretical analysis of teachers training to profession, including teacher of technology, research has been carried out. The basic components of teacher training are outlined, the meaning of "professional and pedagogical training of teachers", "professional teacher", "teaching ability" terms is highlighted. The attention is focused on professional and pedagogical competence of the teacher as a set of teacher's skills. The basic elements of the professional pedagogical competence of teacher of technologies are highlighted. The basic professional skills of teachers are characterized. The main stages in the system of professional and pedagogical teacher training components are characterized. The main aspects of the training of teachers of technology are described.